DEVELOPMENT OF THE FUNCTIONALITY OF THE CSDP AND THE CRISIS MANAGEMENT OF THE EUROPEAN UNION (Annual of the Faculty of Philosophy in Skopje, 2022)
Within the institutional structure of the EU, there are both relations of cooperation and competition. According to the formula that the form follows the function, the institutions of the Union are a reflection of the goals of the existence of the Union, i.e. their architecture is aimed at achieving the Union’s priorities. The establishment and deepening of a common foreign and security policy has been challenged by both external and internal challenges. The author tries to point out the late adoption of the Maastricht and Amsterdam agreements and the consequently dysfunctional EU foreign policy in relation to the events in the former Yugoslavia. The thinking is that the EU has been more reactive than active. Questions are raised about the achieved functionality of the Union’s foreign policy action in accordance with the developed instruments in the security and defence policy in the following years; then why does the Member States have not been able to achieve the initial Headlines Goals set; as well as fears that an independent European security pillar would diminish NATO’s importance. The available data indicate that the continuous development of the CSDP and the EU crisis management are institutionally and functionally related to NATO, with the two institutions being separable but not separate.
Keywords: EUROPEAN UNION; CFSP; CSDP; CRISIS MANAGEMENT; NATO